Application of Near-Infrared spectroscopy and chemometric (PCA) in variety holothuria atra and holothuria scabra in Simeuleu, Aceh province. Issue 1 (February 2021) - Ikhsan, I; Yusnaini, R; Nasution, R; Munawar, A A; Idroes, R
Abstract: As the largest maritime country globally, Indonesia has a variety of potential marine biota that can be explored as a source of nutrition and raw materials for medicine. As one of the marine biota, Sea cucumbers have been widely recognized by the public as a medicine for treatment from generation to generation. With the breadth and variation of Indonesian waters' characteristics, it is possible to have differences in the nutritional and bioactive content of various types and sources of sea cucumber. This study analyzes the compounds in Holothuria atra, and Holothuria scabra dried sea cucumbers using Near-Infrared Spectroscopy (NIRS). Spectrum data of dried sea cucumber samples were obtained from the absorbance spectrum in the wavelength range of 780 nm - 2500 nm with a resolution of 0.02 nm and 32 scans. The spectrum data is then projected onto principal component analysis (PCA) to extract data and observe similarities between the two samples. The results showed that there was no difference between the Holothuria atra and Holothuria scabra dry samples in terms of the spectral data showing their molecular bonds. However, the essential chemical structure related to the content of sea cucumbers is vibrating in the Near-infrared region, especially in the waves 1147, 1310, 1452, 1667, 1819, 1920, and 2235 nm, indicates the presence of molecular bonds C-H, O-H, C-O, C-H-O, N-H, and S-H. Based on the results obtained, it can be concluded that NIRS has the potential to analyze and determine several quality attributes of sea cucumber samples with further calibration modeling.